Is Aquaculture a Path to Community Resilience in Maine? - Cotton, Benjamin; Noblet, Caroline; Wyatt, Bruce; Evans, Keith; Teisl, Mario (Maine Policy Review, 2023)
Coastal towns across Maine face a number of challenges maintaining resilience, posing a threat in their response to disaster. Aquaculture has been presented as a potential solution for some coastal communities; however, the question of ‘fit’ is a source of debate within Maine. Decision-makers may seek further understanding of citizens’ perceptions of their community’s resilience and marine aquaculture, including preferences for supporting growth of the sector across the state's coastal region. To provide this information, we analyze data from a survey of Maine citizens. We assess residents’ perceptions of community resilience and whether marine aquaculture supports resiliency goals along the coastline of Maine.
Keywords: Aquaculture; Community Resilience; Sustainability